Dopaminergic modulation of motor network compensatory mechanisms in Parkinson's disease. Issue 15 (10th July 2019) - Jastrzębowska, Maya A.; Marquis, Renaud; Melie‐García, Lester; Lutti, Antoine; Kherif, Ferath; Herzog, Michael H.; Draganski, Bogdan
Abstract: The dopaminergic system has a unique gating function in the initiation and execution of movements. When the interhemispheric imbalance of dopamine inherent to the healthy brain is disrupted, as in Parkinson's disease (PD), compensatory mechanisms act to stave off behavioral changes. It has been proposed that two such compensatory mechanisms may be (a) a decrease in motor lateralization, observed in drug‐naïve PD patients and (b) reduced inhibition ‐ increased facilitation. Seeking to investigate the differential effect of dopamine depletion and subsequent substitution on compensatory mechanisms in non‐drug‐naïve PD, we studied 10 PD patients and 16 healthy controls, with patients undergoing two test sessions — "ON" and "OFF" medication. Using a simple visually‐cued motor response task and fMRI, we investigated cortical motor activation — in terms of laterality, contra‐ and ipsilateral percent BOLD signal change and effective connectivity in the parametric empirical Bayes framework. We found that decreased motor lateralization persists in non‐drug‐naïve PD and is concurrent with decreased contralateral activation in the cortical motor network. Normal lateralization is not reinstated by dopamine substitution. In terms of effective connectivity, disease‐related changes primarily affect ipsilaterally‐lateralized homotopic cortical motor connections, while medication‐related changes affect contralaterally‐lateralized homotopic connections. Our findings suggest that, in non‐drug‐naïve PD, decreased lateralization is no longer an adaptive cortical mechanism, but rather the result of mal adaptive changes, related to disease progression and long‐term dopamine replacement. These findings highlight the need for the development of noninvasive therapies, which would promote the adaptive mechanisms of the PD brain.